Comparative Analysis on the Elastic Behavior of Composite Materials Based on Plant Fibers: Bamboo / Epoxy and Coconut / Epoxy - Mokaddem, Allel; Doumi, Bendouma; Belkheir, Mohammed; Touimi, Amina (Current Materials Science, 2019)
Background: The exploitation by the industries of vegetable fibers in the field of composite materials has made it possible to reduce the dependency of oil which is the result of their mechanical properties, their thermal resistance and biodegradability. Methods: In this work, we carried out a comparative study by a genetic simulation on two materials based on different natural reinforcements (Bamboo and Coconut) to see the influence of its fibers on the elastic behavior of bio-composite materials. Results: The results of our genetic simulation showed that Bamboo / Epoxy is more resistant than Coconut / Epoxy and that shear damage of Bamboo / Epoxy is lower than that of Coconut / Epoxy by 11 to 12.5%. Conclusion: The results are similar to the results given by Rao KMM where he showed by experimental tests that Bamboo fiber is the most resistant when compared with other fibers especially coconut fiber.
Keywords: bamboo